(untitled) (Cadernos de Sociomuseologia, 2012)
The presentation will focus on ICOM Switzerland‘s works concerning training designed for museums professionals. Its implication in this field is increasing, within the framework of its own offer of continuous education, as well as within partnerships with other external institutions (for example universities).In September 2008, the first Master in Museology in Switzerland (Master en études muséales) will be launched, as a result of the cooperation of ICOM Switzerland, the University of Neuchâtel and l‘Association des musées suisses (the National Swiss Museums Association).ICOM Switzerland is involved in reflections with museum professionnals. For instance, it collaborated with Swiss museum educators (the médiateurs culturels) in order to define quality standards for their working areas. This year also, a certification has also been set up, regarding training for museums professionals. The project has been presented in Vienna last year and it is now operational.